Annie Leibovitz at work - Leibovitz, Annie, 1949- (Phaidon Press Limited ; Phaidon Press Inc., 2018)
Annie Leibovitz in her own words. A revised and updated edition of the classic account of how the most celebrated photographer of our time makes her pictures. Text based on conversations with Sharon DeLano.
Keywords: Leibovitz, Annie, -- 1949-; fotografky -- 20.-21. století -- Spojené státy americké; portrétní fotografie -- 20.-21. století -- Spojené státy americké; umělecká fotografie -- 20.-21. století -- Spojené státy americké; osobnosti -- 20.-21. století; portréty; fotografování; fotografické techniky; women photographers -- 20th-21st centuries -- United States; portrait photography -- 20th-21st centuries -- United States; artistic photography -- 20th-21st centuries -- United States; celebrities -- 20th-21st centuries; portraits; photography; photographic techniques; autobiografické vzpomínky; fotografické publikace; autobiographical reminiscences; photographical works